2010
DOI: 10.1186/1477-5956-8-59
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of streptomycin resistant and sensitive clinical isolates of Mycobacterium tuberculosis

Abstract: BackgroundStreptomycin (SM) is a broad spectrum antibiotic and is an important component of any anti-tuberculosis therapy regimen. Several mechanisms have been proposed to explain the emergence of resistance but still our knowledge is inadequate. Proteins form a very complex network and drugs are countered by their modification/efflux or over expression/modification of targets. As proteins manifest most of the biological processes, these are attractive targets for developing drugs, immunodiagnostics or therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…In another study, four proteins Rv0635, Rv1827, Rv0036c, and Rv2032 were identified as intracellular MDR-TB and two proteins of Rv2896c and Rv2558c were belonged to sensitive isolates (Neelja et al, 2012). One other study found nine proteins as overexpressed in SM-resistant isolates consisting of Rv0350, Rv0440, Rv1240, Rv3057c, Rv3028c, Rv2145c, Rv2031c, and Rv0569 (Sharma et al, 2010). These results are approximately similar to our findings.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In another study, four proteins Rv0635, Rv1827, Rv0036c, and Rv2032 were identified as intracellular MDR-TB and two proteins of Rv2896c and Rv2558c were belonged to sensitive isolates (Neelja et al, 2012). One other study found nine proteins as overexpressed in SM-resistant isolates consisting of Rv0350, Rv0440, Rv1240, Rv3057c, Rv3028c, Rv2145c, Rv2031c, and Rv0569 (Sharma et al, 2010). These results are approximately similar to our findings.…”
Section: Discussionsupporting
confidence: 95%
“…Automated two-dimensional electrophoresis coupled with MALDI-TOF-TOF (matrix-assistedlaser desorption/ionization) has proven to be very efficient in the analysis of complex protein/peptide mixtures. In contrast to conventional protein sequencing procedures; mass spectrometry allows the rapid and automated analysis of many proteins in a short time frame (Shevchenko et al, 1996(Shevchenko et al, , 2006.…”
Section: Experimental Articlesmentioning
confidence: 99%
“…The third drug in our study is the aminoglycoside antibiotic streptomycin, which targets protein synthesis by direct interaction with the small ribosomal subunit [11]. Streptomycin was the first drug used in the treatment of Mycobacterium tuberculosis and is preferred for treatment of relapses [12]…”
Section: Introductionmentioning
confidence: 99%
“…Coexpression and Occurrence analysis for this protein was obtained from STRING database. Blastp analysis [27] against a human protein database was done to validate that this particular protein not share any homology with human proteins.…”
Section: Methodsmentioning
confidence: 99%